Emerging roles and therapeutic potential of tRNA-Derived small RNAs in reproductive system diseases: a review - Zhou, Qian; He, Minxin; Liu, Min; Sun, Guoying; Li, Jian (Frontiers in Cell and Developmental Biology, 2025)
tRNA-derived small RNAs (tsRNAs) are a class of non-coding RNAs(ncRNAs) generated from precursor or mature tRNAs under stress conditions, such as starvation, hypoxia, or oxidative stress. They are broadly classified into a growing class of small RNAs, known as tRNA-derived RNA (tDR), tRNA-derived small RNAs or tRNA-derived fragments and tRNA-derived stress-induced RNAs (tiRNAs) based on their cleavage sites. Recent advances in high-throughput sequencing have revealed their critical roles in the reproductive system, particularly in spermatogenesis, sperm maturation, and male infertility. In females, tsRNAs are implicated in oocyte development and embryo implantation. Dysregulation of tsRNAs has also been linked to reproductive diseases, including polycystic ovary syndrome (PCOS) and endometriosis in women, and oligospermia or azoospermia in men. Mechanistically, tsRNAs regulate gene expression, mRNA stability, and translation, influencing key pathways in reproductive health and disease. Their potential as biomarkers and therapeutic targets for reproductive disorders is increasingly recognized, though further research is needed to fully elucidate their roles and clinical applications.